Institutional risk management, financial fragility and market structure in the banking firm: theories, regulation effects and international evidence - Ruiz Porras, Antonio (2004)
We study the behaviour of banking intermediaries focusing on the joint relationships among risk management, fragility and the market structure. Theoretically, we use the industrial organisation approach to analyse the relationships between banking behaviour and risk management goals and between banking behaviour and regulation effects. We develop and calibrate models to study the monopolistic competition effects on banking stability and to study the effects of asset and liability uncertainty on banking decisions. We extend such analyses to study the effects caused by portfolio restrictions and deposit interest-rate regulations on banking behaviour. Empirically, we characterise the financial and banking stylised facts associated to stable and unstable banking systems. Furthermore, we assess among competing theories and policy views regarding the relationships between banking stability and management practices, and between fragility and banking market structure. The empirical study relies on OLS regressions and random effects logit models for panel data. The dataset includes data for a sample of 47 countries during the period 1990-1997.